Antioxidant Activity Modulated by Polyphenol Contents in Apple and Leaves during Fruit Development and Ripening - Wojdyło, Aneta (Antioxidants (Basel), 2020)
Apples (Malus domestica Borkh) are of particular interest for their high content of healthy phytochemicals. This study investigated the antioxidant activity and polyphenolic compounds of extracts from the fruits from Ozark Gold, Starkinson and Kosztela cultivars and additionally leaves from Ozark Gold cv. Phenolic compounds were identified and quantified by liquid chromatography- mass spectrometer (LC–MS) and high pressure liquid chromatography (HPLC). The samples were collected during fruit development at 60, 80, 130 and 145 days after full bloom. The concentration of apple phenolics was highest early in the season and decreased during fruit development. The leaf phenolics had a more steady level during all the period of collection than the fruits. Among the five groups of analyzed polyphenols, the procyanidins predominated in apple fruits and dihydrochalcones in leaves. The concentration of polyphenols decreased from 39.15, 5.97 and 33.39 g/kg dw (collected at 60 days after full bloom) to 14.22, 2.05 and 9.31 g/kg dw (collected at 145 days after full bloom) for apples Ozark Gold, Starkinson, Kosztela, respectively. The leaves characterized a much higher content of polyphenolic compounds and antioxidant capacity than unripe fruits. Antioxidant capacity measured by 2,2-azinobis-(3-ethyl-benzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-picrylhydrazyl (DPPH) methods was higher when the apple was unripe and the leaves were young. The results indicate that, unripe fruits and leaves are very good raw material for polyphenol nutraceutical production with high antioxidant potential.